Bayes decision theory based risk minimization authorization mapping - Bin ZHAO; Jing-sha HE (Tongxin xuebao)
Authorization decision was one of the key issues in the control access.In order to effectively enhance the security of authorization in trust based access control authorization,according to minimization risk Bayes decision theory,authorization was the object to the subject in access control as found that the problem of optimal decision.A method that minimizates risk based authorization mapping to realize correct authorization operation in the access control was proposed.Example analysis and simulation experiment show that the method is able to reduce risk accurately to interaction final authorization.